The CN-12: A Brief, Multidimensional Connection With Nature Instrument - Hatty, Melissa Anne; Smith, Liam David Graham; Goodwin, Denise; Mavondo, Felix Tinoziva (Frontiers in Psychology, 2020)
In recent decades, there has been increasing interest in (re)connecting people with nature to foster sustainability outcomes. There is a growing body of evidence suggesting a relationship between connection with nature and pro-environmental behaviors. Connection with nature has often been conceptualized as a unidimensional construct, and while recent evidence suggests it is multidimensional, there is ongoing debate regarding the dimensions that make up connection with nature. Existing multidimensional connection with nature instruments capture similar dimensions yet they are lengthy and may not have practical application in real-world contexts. This research sought to clarify the dimensions of connection with nature, and to develop and validate an abbreviated yet multidimensional connection with nature instrument – the CN-12. Analyses of two large data sets revealed three dimensions of connection with nature – Identity, Experience, and Philosophy. Results suggested the CN-12 and its three dimensions are positively correlated with: 1) environmental and altruistic values; 2) time spent in nature; and 3) a range of pro-environmental behaviors. Results also suggested that the CN-12 and its three dimensions are stable over time, and are positively correlated with two existing multidimensional connection with nature instruments, the Nature Relatedness Scale (NR) and Environmental Identity Scale (EID). The utility of the CN-12 for exploring human connections with nature, and the role of fostering connection with nature to increase engagement in pro-environmental behaviors, are discussed.